DIAGNOSTIC ACCURACY OF SPERM DNA FRAGMENTATION INDEX IN MALE INFERTILITY: A COHORT STUDY: SPERM DNA FRAGMENTATION INDEX IN MALE INFERTILITY - Zhang, Juan; He, Wei (Journal of Medical Biochemistry, 2025)
Objective: To explore the correlation of sperm DNA fragmentation index (DFI) with semen quality, while assessing the diagnostic potential of DFI in male infertility, aiming to offer a novel biomarker and clinical approach for male fertility evaluation.Methods: A cohort of 613 men who visited our hospital between April 2023 and February 2025 was included in this study. Semen analysis (assessing concentration, motility, morphology, etc.) and sperm chromatin dispersion testing were conducted to determine DFI. The diagnostic performance of DFI for infertility was evaluated using receiver operating characteristic (ROC) curve analysis. Subgroup analyses (oligozoospermia, asthenozoospermia, and oligoasthenozoospermia) were conducted to assess the discriminative power of DFI. After treatment, the patients were followed up for 1 year, and the predictive effect of DFI on the prognosis of successful fertility was analyzed.Results: Among infertile men (n=92, incidence rate: 15.01%), DFI levels were significantly elevated compared to those with normal fertility (P
Keywords: male infertility; sperm DNA fragmentation index; sex hormones; semen parameters; diagnosis